Improving Student's Skills and Concept Understanding in Vibration and Waves with the Use of Visual Media Concepts on Students - Asep Sopandi; Anna Permanasari; Indarini Dwi Pursitasari (Universitas Pakuan, 2022)
This research was conducted to determine the effectiveness of the media in improving science process skills. The effectiveness of visual media was further investigated using the Quasi-Experimental method with a pre-post test control group design. Learning is carried out using a cooperative model of investigative group type. The population is all students of class VIII of one junior high school in West Java academic as many as 324 students. This study aims to develop GI type cooperative learning to improve students' process skills and concept mastery. Science was compiled using cooperative learning with group investigation, but non-visual media in the control class. The results showed that visual media can improve science process skills and mastery of vibration and wave material concepts. It can be seen that the N-Gain value is 55% for science process skills (medium category) and 67% (medium category) for concept mastery. Conclusion of the research can be seen that the use of visual media material vibrations and waves in cooperative learning investigative group type can improve skills, mastery of concepts and motivate students to be active in learning compared with investigative group type cooperative learning without the use of visual media.